The Influence of Service Quality, Religiosity, and Trust on Muzakki's Interest in Paying Zakat Maal at LAZ RIZKI Jember - Moehammad Fathorrozi; Bahrina Almas; Devi Camelia Gustinada (Journal of Islamic Philanthropy and Disaster (JOIPAD), 2025)
Introduction: This study aims to analyze the influence of service quality, religiosity, and trust on the interest of muzakki in paying zakat maal at LAZ RIZKI Jember. Research Methods: This study adopted a quantitative approach, utilizing multiple linear regressions as the statistical analysis method to examine the relationships between service quality, religiosity, and trust and the interest of muzakki in paying zakat maal. Results: This study reveals that service quality and trust significantly influence muzakki's interest in paying zakat maal through LAZ RIZKI Jember. Religiosity does not significantly influence muzakki's interest in paying zakat through LAZ RIZKI, which shows that a person's level of faith is not the main factor in the decision to pay zakat through the institution. Conclusion: Simultaneously, these three variables contribute to determining the interest of muzakki. Consequently, LAZ RIZKI Jember should prioritize enhancing transparency, streamlining service delivery, and fortifying institutional trustworthiness to foster greater participation and optimize muzakki engagement.